The Effect of Work Culture, Leadership and Rewards on Employee Performance in Companies in West Java, Mediated by Motivation - Rieki Indra Bratamanggala; Supardi Supardi (Dinasti Publisher, 2026)
This study is motivated by the importance of improving employee performance within organisations, which is influenced by various factors such as work culture, leadership, rewards, and motivation. In practice, there remains inconsistency in research findings regarding the influence of these variables on employee performance, thus necessitating further empirical study. This study aims to analyse the influence of work culture, leadership, and rewards on employee performance, with motivation as a mediating variable. The research method employed is a quantitative approach using an explanatory research design. Data were collected through the distribution of questionnaires to respondents and analysed using Partial Least Squares-based Structural Equation Modelling (SEM-PLS). The results indicate that work culture has a positive and significant effect on motivation, and that leadership has a positive and significant effect on employee performance. However, work culture does not have a significant effect on performance; leadership does not affect motivation; motivation does not affect performance; and rewards do not have a significant effect on either motivation or performance. These findings contribute to an understanding that leadership and work culture play a strategic role in enhancing motivation and performance, although the mediating role of motivation has not been proven to be significant. This study concludes that organisations need to focus on strengthening leadership and work culture, as well as evaluating the reward system to make it more effective. Further research is recommended to include additional variables and expand the scope of the study to obtain more comprehensive results.